Neonatal lupus erythematosus presenting as orolabial ulcerations: Two cases and a review of the literature. Issue 3 (5th March 2021) - Drohan, Alex; Snyder, Alan; Plante, John; Karlin, Samantha; Wine Lee, Lara; Cotton, Colleen H.
Abstract: We report two unrelated infants who presented with orolabial ulcerations as a presenting manifestation of neonatal lupus erythematosus (NLE). Subsequent positive anti‐SSA/SSB titers confirmed the diagnosis. In both infants, the ulcerations were painless and spontaneously resolved. NLE should be included in the differential diagnosis of orolabial ulcerations in the newborn, especially since mothers of affected infants may be asymptomatic.